Consumer Legal Protection in Telecommunication: Doctrinal and Comparative Insights from Indonesia and Spain - Anggreany Arief; Asriati Asriati; Sahban Sahban; Retno Sari Dewi; Antonio Gutiérrez-Pozo (Fiat Justisia: Jurnal Ilmu Hukum, 2026)
Digital transformation has turned telecommunications into essential infrastructure for social and economic life. This shift creates legal challenges, including consumer inequality, opaque electronic contracts, data protection risks, and ineffective dispute resolution. This study compares telecommunications consumer protection frameworks in Indonesia and Spain, focusing on regulatory effectiveness, supervisory institutions, and consumer rights in the digital era. Using doctrinal and comparative analysis, it examines national legislation, legal instruments of the European Union, and reports from telecommunications regulators. The findings show that Spain has developed a more integrated and adaptive system through regulatory harmonization, particularly in contract transparency, data protection, and enforcement of provider obligations. Indonesia still faces institutional fragmentation, weaker enforcement, and slower regulatory adaptation to technological change. Strengthening protection in Indonesia requires reforms focused on digital rights, independent oversight, and efficient dispute resolution. These findings contribute to digital consumer protection scholarship and offer policy guidance for technology-driven economies..